(untitled) (Journal of Dhaka Medical College, 2024)
Introduction: Idiopathic granulomatous mastitis (IGM) is a rare, benign, and chronic inflammatory breast condition that has been shown to have radiological and clinical similarities to breast cancer. In spite of the fact that the cause of IGM is unknown, various contributing variables have been identified, such as a reaction to chemical substances like OCP, viral disorders, autoimmune diseases, and an immunological response to milk leakage from the breast lobule. Although various methods have been used for IGM treatment (such as surgical excision, steroids, methotrexate, etc), no consensus currently exists regarding the ideal method of treatment. Due to its positive response to steroid treatment, it is hypothesized that IGM is an autoimmune disease and is well responds to corticosteroid therapy. The aim of this study is to observe the treatment outcomes of surgery and corticosteroid therapy in IGM. Materials and Methods: This quasi experimental study was conducted in Department of Surgery, Khulna Medical College Hospital from 8th August 2018 to 8th August 2019. Total 30 patients were enrolled and allocated in two groups a ratio of 1:1. In group-A there were 15 patients, received surgical treatment with corticosteroid therapy and group-B, 15 patients received only surgical treatment. A wide local excision (WLE) was done in surgical procedure to remove area of diseased unhealthy tissue with a margin of normal tissue. Corticosteroid therapy was given orally in the following regimen: 8 weeks of steroid therapy with prednisolone at 0.5mg/kg/day for 4 weeks and then tapered down slowly for 4 weeks. Then subsequent follow up conducted after 2 months and after 4 months of primary treatment to observe the treatment outcomes. Statistical analysis was carried out by using the Statistical Package for Social Sciences version 23.0 for Windows (SPSS Inc., Chicago, Illinois, USA). A descriptive analysis was performed for all data. The mean values were calculated for continuous variables. The quantitative observations were indicated by frequencies and percentages. Unpaired student t-test was used to compare continuous variables. Chi-square test used to compare categorical data. A “p” value of <0.05 was considered as significant. Result was presented by tabulation and graphical presentation in the form of tables, pie chart, graphs, bar diagrams, histogram & charts etc. Result: Maximum numbers of patients (50.0%) were between 31-40 years age group, mean±SD age was 29.7±10.2 years. The left breast was affected in 16(53.3%) patients, right breast in 12(40.0%) patients and bilateral in 2(6.7%) patients. Included 30 patients were allocated in two groups. Among them in group-A there were 15 patients (Surgical treatment with corticosteroid therapy) and group-B, 15 patients (Surgical treatment alone). Wide local excision was performed in all patients. Concomitant corticosteroids therapy was used in selective group (group-A). Study shows that 22(73.3%) of the patients recovered completely (80.0% versus 66.7% in group-A and group-B respectively). There was a statistically significant difference (pd”0.05). Present study revealed that incidence of complications and recurrence rate was 8(26.7%) patients, among them 3(20.0%) were of group-A, while 5(33.3%) patients were group-B. Conclusions: Present study concluded that treatment outcomes of surgery, followed by corticosteroid therapy can be preferred at Idiopathic granulomatous mastitis (IGM) in the means of less early or late postoperative complication, resolution of symptoms with high accuracy rate to relief symptoms. J Dhaka Med Coll. 2023; 32(1) : 71-76